2016
DOI: 10.3892/ol.2016.4887
|View full text |Cite
|
Sign up to set email alerts
|

Physical exercise modulates the level of serum MMP-2 and MMP-9 in patients with breast cancer

Abstract: Abstract. Matrix metalloproteinases (MMPs) exhibit an important function in extracellular matrix degradation. MMPs modulate the activation of growth factors, cytokines and metastasis. At present, the effect of exercise on serum levels of MMP-2 and -9 remains unclear. The aim of the present study was to investigate the effect of various physical activities on the circulating levels of MMP-2 and -9 in breast cancer (BC) survivors and healthy subjects. A total of 66 female subjects were enrolled in the present st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
24
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 64 publications
2
24
0
3
Order By: Relevance
“…The change in MMP-9 reported here is similar to previous exercise studies in non-cancer 17 and cancer populations 18 (the latter was an observational study). Kadoglou et al (2010) reported a significant within-group decrease in serum MMP-9 after a 16-week supervised endurance training program (30-60 min of brisk walking; 4 days/ week) in patients with type 2 diabetes 17 .…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The change in MMP-9 reported here is similar to previous exercise studies in non-cancer 17 and cancer populations 18 (the latter was an observational study). Kadoglou et al (2010) reported a significant within-group decrease in serum MMP-9 after a 16-week supervised endurance training program (30-60 min of brisk walking; 4 days/ week) in patients with type 2 diabetes 17 .…”
Section: Discussionsupporting
confidence: 88%
“…MMP-2 and -9 are reduced with exercise interventions in patients with type 2 diabetes 17 and breast cancer 18 ; other MMPs such as MMP-1, -7, -9, TIMP-1 and -2, have not been determined whether exercise improves the level of MMPs in clinical populations such as type 2 diabetes. While there is evidence showing that moderate-intensity aerobic exercise training may decrease MMP-2 and -9 levels in clinical research settings 17,18 , the effects of high intensity interval training (HIIT) on MMP levels have not been investigated in any population. HIIT is an exercise strategy that maximizes exercise intensity by using bursts of concentrated effort alternated with recovery periods 19 .…”
mentioning
confidence: 99%
“…The proteases, such as matrix metalloproteinases, are, therefore, considered as a key factor in this process 31,32. Moreover, protease inhibitors are generally expected to have an antimalignant role 33.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, MMP-2 and MMP-9 are gelatinases that degrade type IV collagen, the major structural component of the ECM [4]. These proteases were found to take part in many ocular disorders like retinopathy [5], cataract [6], uveitis [7], or generally atopic ocular diseases [8].…”
Section: Introductionmentioning
confidence: 99%